Proctitis and Abdominal Aortic Aneurysm: Six Degrees of Separation - Kolli, Sindhura (Cureus, 2019)
Cytomegalovirus (CMV) is an aggressive virus responsible for a considerable amount of case fatalities. In the overwhelming majority of cases, this affects only the immunocompromised. Herein, we present a 76-year-old immunocompetent female who presented with gastrointestinal bleeding found to have rectal ulceration secondary to CMV infection. This manuscript aims to raise awareness of a rare cause of rectal bleeding. Hopefully, as such, our case will also prevent long-standing inflammation from persisting in patients with CMV and prevent it from contributing to cardiovascular pathology as seen in our patient.